Transition economies : political economy in Russia, Eastern Europe, and Central Asia - Myant, M. R. (Martin R.); Drahokoupil, Jan, 1980- (Hoboken, N.J. : Wiley, 2011)
'Global business managers will explore the economic transformation in former communist countries of Eastern and Central Europe and countries of the former Soviet Union with this book. It takes them from the end of central planning to the capitalist varieties of the present. It covers differences between countries in terms of economic performance and integration into the world economy. The chapters examine these differences in terms of historical backgrounds, location and policies pursued. Attention is placed on state forms and the role of the state in development, to political forms and interest representation and to the development of new forms of business organization. This will provide global business managers with a basis for identifying and explaining changes between groupings of countries in Eastern Europe and the former Soviet Union.'--
Includes bibliographical references and indexes.
Keywords: Mixed economy -- Russia (Federation); Mixed economy -- Europe, Eastern; Mixed economy -- Asia, Central; Russia (Federation) -- Economic conditions -- 1991-; Europe, Eastern -- Economic conditions -- 1989-; Asia, Central -- Economic conditions -- 1991-